(untitled) (International Conference on Computers in Education, 2022)
This thesis focuses on the design of a Chinese learning system developed using the Unity platform and experiments to test the validity. The validity of the Mixed Reality (MR) learning system was verified by examining the learners’ Chinese test levels before and after learning with the MR system, as well as the general affective scale and behavioral engagement and emotional engagement scale for each section of the learning. The results were that learning through the MR system resulted in a significant increase in comprehension and a higher level of positive emotion in the game session with physical participation than in the pronunciation session alone. However, due to the current too small sample size, there was an intentional difference in the overall validity of the negative and emotional engagement. Still, none of the multiple comparisons found a calculated difference.